THE The Use of Music Background in Teaching Reading Comprehension for Negative and Positive Students’ Perception - Saefudin, Dery Purnama; Saleh, Mursid; Warsono, Warsono (English Education Journal, 2019)
Reading is a kind of activity to transfer the information and to comprehend the writer’s ideas by the learner through the written or the printed words. Learning achievement is not only determined by the one factor such as teaching method, but also it is affected by some learning factors. Besides, learning is affected by psychological factor such as classroom atmosphere.This study used experimental research. It was aimed to comparing the effectiveness of Beta Wave music, acoustic music, no music, as music background when learning English. This study was experimental research by using factorial design, it was 3x2 factorial design and use technique of multi factor analysis of variance (ANNOVA) which helped to understand the effect of two or more independent variables upon a single dependent variable, the independent variables are beta wave music, acoustic music, and no music, and the dependent variable is the students’ achievement in reading comprehension of tenth graders of SMAN 4 Kota Cirebon. For moderating variables are positive and negative students’ perception toward music background.Mostly, students with positive perception were affected by music background whether acoustic and beta wave music as well as none-music background in learning reading comprehension.While students with negative perception were positively affected even a few students were negatively affected by beta music background when they learn reading comprehension. Because, they thought that the music were annoying, then the students felt uncomfortable. But it was different with students with negative perception in experiment A that used acoustic music background. They were positively affected by acoustic music background.The use of acoustic melodic music was effective in developing students’ reading comprehension both of students with positive and negative perception toward. While the use of beta wave music background was effective in developing students’ reading comprehension for students with positive perception but it was not effective for students with negative perception.